PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMA NEGERI 12 PADANG - Putri, Nadia; R., Syahrul; Afnita, Afnita (Universitas Negeri Padang, 2018)
ABSTRACT The purpose of this reseach is to explain the effect of discovery learning through audiovisual media toward writing skill on biographical text for ten grade of SMA Negeri 12 Padang students. This research used quantitative method which usedone group pretest and posttest design. The population of this reseach was the ten grade students of SMA Negeri 12 Padang. There was 325 population but there was only class to be the sample. It was class X IPA 4 whivh consisted of 30 students that choosen by using purposive random sampling technique. The data of this research was the score of the result of students’ writing skill in biographical text before and after using discovery learning model throught audiovisual media. There are three result of this research. First, the students’ writing skill in biographical text before using discovery learning through audiovisual media was 53.65. Second, the students’writing skill biographical text after using discovery learning through audiovisual media was 80,11. Third, based on the t-test alternative hypothesis (H1) is accepted on the significant degree 95% and degree (dk) = n-1 tcount> ttable (1,75>1,70). Kata kunci: discovery learning, media audiovisual, keterampilan menulis teks biografi